(3QSGdI aj GdbhdfLs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3hgj KeGfjI YTQ HGHkG GdHGH GdChd ai Cf CcKQ ef Jcde ef GdGWHGA bGd eMeO Hf RcQjG Ef CcKQ ef bGd ai hLY GdbhdfL aef bQGQ cJHge s
(3BNQgG (B:s
(3GdHGH GdKGfi YTQ ai GdYdGeGJ GdefPhQI jchf GdbhdfL Cbhd Cf eeG jfPQ jchf GdbhdfL SbhW TghI GdWYGe afNJeg HMeO Gddg hGgH GdYbd s
(3Vef eLehY , JQJjHgG (B: (3GdQSGdI GdQGHYI hGdYTQhfs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3eUOQ GbJfGA GdCUd (B:s
(3eLdS ThQGi (B(568) s
Keywords: (3GdWHs